Research and application of fiber fracturing and fiber temporary plugging technology for deep shale gas - HU Junjie, LU Cong, GUO Jianchun, ZENG Bo, GUO Xingwu, MA Li, SUN Yuduo (Youqicang pingjia yu kaifa)
With technological advancements, fibers now serve roles beyond proppant backflow prevention, including proppant transport, plugging, fracture morphology optimization, and other aspects, namely, fiber-network proppant fracturing technology. The fiber-based proppant transport and fiber temporary plugging technologies can effectively address issues currently faced by deep shale gas, such as proppant near-wellbore accumulation and insufficient temporary plugging effectiveness, thereby improving the effectiveness of volumetric fracturing stimulation. To this end, the study was conducted in a deep shale gas block in the southern Sichuan Basin, investigating fiber-based proppant transport and fiber temporary plugging mechanisms, as well as laboratory physical simulations to optimize and evaluate the performance of fiber materials. Based on the regional geological and engineering characteristics of the study area, fracturing software simulations were carried out to determine the hydraulic fracture width for deep shale gas. A field test plan was then developed, and the fracturing construction, flowback, plugging, and fracturing effectiveness of the test wells were monitored and evaluated. The research results indicated that fibers had strong proppant transport assistance and flexible bridging capabilities. By modifying the molecular structure of fiber materials and adding a certain amount of structural stabilizers, discontinuous cluster-like support structures can be formed, significantly enhancing the placement effect and conductivity of proppants. Based on fracture width simulation calculations, the hydraulic fracture width for deep shale gas is between 2 to 5 mm. By optimizing fiber types based on fracture width, proppant grain size, and concentration, full support of fractures can be achieved. Compared to conventional fracturing wells, the test wells with modified fiber + structural stabilizer for sand-carrying fracturing exhibited better production increase and proppant flowback prevention. Fibers can be used for temporary in-fracture plugging. During the construction process, the pressure response is evident, which may lead to excessively high pressure during subsequent operations, making proppant addition difficult. Optimizing the timing of fiber injection is beneficial for the subsequent overall sand addition process. Additionally, fibers can also be used to address the inter-well gas migration issue in deep shale gas wells by strengthening the temporary plugging of fracture openings and sealing natural fractures, thereby preventing further communication between hydraulic fractures and distant natural fractures. The study, based on the characteristics of deep shale reservoirs in the southern Sichuan Basin, has developed a set of performance indicators for fiber materials suitable for deep shale gas, including fiber length, stability, compatibility, and degradation rate. It also proposes a four-in-one fiber injection process and design method, focusing on “entry, distance, height, and prevention”. It provides strong support for the future economic development, technology optimization, and fracturing process adjustments of shale gas.